Integrasi Nilai-Nilai Islam dalam Pengembangan Ilmu Pengetahuan Modern: Sebuah Pendekatan Berbasis Islamic Worldview - Handayani, Fitria; Azahara, Dina Nadya (Journal of Information Systems and Management (JISMA), 2025)
Islamization of science is a movement to integrate Islamic values and principles into various disciplines, aiming to create knowledge that is in accordance with Islamic ethics and morality. In the context of globalization and rapid modernization, challenges to the application of science based on Islamic teachings are increasing. This research explores the relationship between worldview, paradigm, and theory in the process of Islamization of science. Using qualitative and descriptive research methods with note-taking techniques, analysis of literature and thoughts from key figures such as Imre Lakatos and Syed Muhammad Naquib al-Attas, this article focuses on how Islamic values can be integrated in the development of scientific theories and methodologies. The results show that the Islamization of science involves not only changing the content of science, but also the approach used in research. In addition, resistance from secular thought is a major challenge in the implementation of Islamization. This study concludes that the Islamization of science can produce knowledge that is not only academically useful, but also supports moral and ethical commitments, which are important for creating a generation of Muslim scientists with integrity.